2002
DOI: 10.1088/0953-8984/14/39/101
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation-induced metastable phase formation and amorphization in an immiscible Co/Ag multilayer

Abstract: Co/Ag multilayers were prepared by an alternate deposition of Co and Ag metals using electron beam evaporation. These multilayers were irradiated with 130 keV argon ions at room temperature. Upon irradiation to a fluence of 7 × 10 16 ions cm −2 , a new metastable phase (DO 19 ) with hcp structure having nanosized grains embedded in a matrix having an amorphous structure was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
3
6
0
Order By: Relevance
“…36 Besides, a nonequilibrium fcc structured Ag 3 Co alloy has been formed in thin films upon ion irradiation, 13 and Amirthapandian et al have observed an hcp structured CoAg 3 phase (DO 19 ) in an amorphous matrix in an ion beam mixing experiment. 24,37 In fact, these experimental observations strongly support the above lattice dynamics calculations. From the above calculated elastic constants and phonon spectra, it is concluded that, at a chemical stoichiometry of Co/Ag ) 1:3, the nonequlibrium CoAg 3 compound of either L1 2 or D0 19 structure can be relatively stable under some specific conditions.…”
Section: Comparison With the Ion Beam Mixing Experimentsupporting
confidence: 83%
See 1 more Smart Citation
“…36 Besides, a nonequilibrium fcc structured Ag 3 Co alloy has been formed in thin films upon ion irradiation, 13 and Amirthapandian et al have observed an hcp structured CoAg 3 phase (DO 19 ) in an amorphous matrix in an ion beam mixing experiment. 24,37 In fact, these experimental observations strongly support the above lattice dynamics calculations. From the above calculated elastic constants and phonon spectra, it is concluded that, at a chemical stoichiometry of Co/Ag ) 1:3, the nonequlibrium CoAg 3 compound of either L1 2 or D0 19 structure can be relatively stable under some specific conditions.…”
Section: Comparison With the Ion Beam Mixing Experimentsupporting
confidence: 83%
“…Choosing the Co−Ag system is based on the following considerations. First, it has recently been noted that the granular materials made of Co−Ag alloys feature a giant magnetoresistance (GMR) effect and have a consequent potential for practical applications. , Second, it has been found that though the Co−Ag system is essentially immiscible at equilibrium, an effective intermixing did take place at the Co−Ag interface under some specific circumstance. , Third, a proven realistic Co−Ag potential under the second moment approximation of the tight-binding scheme (TB-SMA) has been constructed and the potential was able to reproduce some static properties as well as to reflect some dynamic properties of the Co−Ag system. 6, 25…”
Section: Introductionmentioning
confidence: 99%
“…Since noble gases have a tendency to diffuse by a vacancy‐assisted mechanism, trapping of the gaseous atoms by bombardment‐induced vacancies could also result in formation of very small bubbles in the form of inert gas vacancy clusters. However, the predicted volume fraction of these small bubbles is expected to be less than 2 vol% as estimated for similar studies elsewhere . A comparison of these results with the diffraction data suggests that although substantial mixing at the interface takes place at higher doses, there is no characteristic peak indicative of formation of crystalline molybdenum silicide.…”
Section: Resultssupporting
confidence: 61%
“…The process termed as ion beam mixing has been used to synthesize metastable phases of materials for variety of applications. The formation of intermetallic phases at the interfaces and the underlying ion induced atomic transport processes under ion beam mixing has been investigated by number of investigators, as the phases formed have many technological applications [1][2][3]. A number of ion beam mixing models have been proposed.…”
Section: Introductionmentioning
confidence: 99%